1999
DOI: 10.1111/1467-9507.00082
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Feelings and Coping with Emotional Situations: A Comparison of Maltreated and Nonmaltreated Preschoolers

Abstract: The effects of maltreatment on children's emotion knowledge (e.g., recognition of facial cues for happy, sad, mad, scared, and surprised expressions), parent-and teacher-rated social and expressive behavior (e.g., aspects of emotion regulation such as emotional intensity, regulation of emotionally-driven behavior, and classroom social competence with peers such as conflict management), and hypothetical social problem-solving skills were examined in a sample of 45 preschool-aged, predominantly African-American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 44 publications
2
48
0
2
Order By: Relevance
“…Izard et al [2001] also present a path analysis suggesting that effects of verbal ability on later aca- Human Development 2003;46:69-96 demic competence are mediated by emotion knowledge, i.e., verbal ability is causally antecedent to emotion ability. Somewhat similarly, Smith and Walden [1999] found that vocabulary correlated (typically at 0.3-0.5: N = 45) with tasks tapping emotion knowledge tasks. They also found that vocabulary mediated effects of deprivation on social-emotional skills, concluding that [p. 106], 'risk status works, at least in part, through cognitive-language development to influence children's social-emotional development'.…”
Section: Abilities For Emotional Adaptivenessmentioning
confidence: 63%
See 1 more Smart Citation
“…Izard et al [2001] also present a path analysis suggesting that effects of verbal ability on later aca- Human Development 2003;46:69-96 demic competence are mediated by emotion knowledge, i.e., verbal ability is causally antecedent to emotion ability. Somewhat similarly, Smith and Walden [1999] found that vocabulary correlated (typically at 0.3-0.5: N = 45) with tasks tapping emotion knowledge tasks. They also found that vocabulary mediated effects of deprivation on social-emotional skills, concluding that [p. 106], 'risk status works, at least in part, through cognitive-language development to influence children's social-emotional development'.…”
Section: Abilities For Emotional Adaptivenessmentioning
confidence: 63%
“…These effects likely reflect modeling as well as inappropriate reinforcement of emotion in the child. More severely maltreated children also have difficulty in coping with stress, and with expressing, recognizing and regulating emotion [Brenner & Salovey, 1997;Smith & Walden, 1999].…”
Section: Reinforcement Of Emotionally Competentmentioning
confidence: 99%
“…Maltreated preschoolers have poorer understanding of universal adult (During & McMahon, 1991) and child facial expressions of emotion (Camras, Grow, & Ribordy, 1983;Camras et al, 1990) and show clear limitations of social cognition in story-stem completion tasks (Macfie, Cicchetti, & Toth, 2001;Macfie et al, 1999). They also manifest a delay in emotion-focused mentalization (Frodi & Smetana, 1984;Pears & Fisher, 2005;Rogosch, Cicchetti, & Aber, 1995;Smith & Walden, 1999), which was found to predict social competence at 8 years of age (Rogosch et al, 1995). Lower oxytocin levels may mediate the apparent undermining of the robust establishment of representations of mental states in maltreated individuals.…”
Section: Oxytocin May Mediate the Relationship Of Attachment And Mentmentioning
confidence: 99%
“…These findings hold regardless of whether emotion knowledge is assessed with emotion recognition tasks where children are asked to identify a facial label after first being given the verbal label or whether the stimuli focus on hypothetical or live events, line drawings, real people or photographs of real people posing emotions, or puppets who "act out " emotions vocally, behaviorally, and contextually (Denham and Couchoud 1990;Fabes et al 2001;Garner and Estep 2001;Michalson and Lewis 1985), but children may perform better if they are asked to interpret emotions of children belonging to their own ethnic group (Glanville and Nowicki 2002). Importantly, these results have been demonstrated in ethnic minority, low-income, and behaviorally maladjustment children (e.g., Downs et al 2007;Garner et al 1994;Smith and Walden 1999).…”
Section: Emotion Knowledge In Early Childhoodmentioning
confidence: 99%